An Analysis Upon Various Treatments For Prevention of Pre-Diabetes With Exercise: Exploring the Relationship Between Physical Activity and Pre-Diabetes (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Prediabetes is acondition that does not fall squarely into the primary or secondary preventiondomain, and therefore tends to be inadequately addressed by interventions ineither health promotion or disease management. Prediabetes is defined as havingan impaired fasting glucose (fasting glucose of 100–125 mg/dL), impairedglucose tolerance (two-hour postprandial glucose of 140–199 mg/dL), or both.There is substantial evidence to suggest that even at these blood glucoselevels, significant risk exists for both micro- and macrovascularcomplications. It’s easy to tell patients to modify their lifestyles tocombat the development of diabetes, but getting them to do so is challenging.Here is specific direction on how to help them succeed. We examined therelationship between PD and objectively measured PA in NHANES 2003–2006 of20,470 individuals, including 7,501 individuals between 20 and 65 yrs.Weexcluded all participants without IFG measures or adequate accelerometry data(final N = 1,317). Participantswere identified as PD if FPG was 100–125 mg/dL (5.6–6.9 mmol/L). Moderate andvigorous PA in minutes/day individuals were summed to create the exposurevariable “moderate-vigorous PA” (MVPA).